Temulence Therapy to Orthotopic Colorectal Tumor via Oral Administration of Fungi‐Based Acetaldehyde Generator. Issue 1 (2nd December 2021) - Zhang, Yu; Zheng, Di‐Wei; Li, Chu‐Xin; Pan, Pei; Zeng, Si‐Min; Pan, Ting; Zhang, Xian‐Zheng
Abstract: Taking inspiration from percutaneous ethanol injection (PEI) for tumor ablation, an acetaldehyde generator (SC@ZIF@ADH) is constructed for tumor treatment by modifying a metal–organic framework nanocarrier (ZIF), which is loaded with alcohol dehydrogenase (ADH), onto the surface of Saccharomyces cerevisiae (SC). Oral administration of SC@ZIF@ADH can target tumor via mannose‐mediated targeting to tumor associated macrophages (TAMs) and generate ethanol at the hypoxic tumor areas. Ethanol is subsequently catalyzed to toxic acetaldehyde by ADH, inducing tumor cells apoptosis and polarizing TAMs toward the anti‐tumor phenotype. In vivo animal results show that this acetaldehyde generator can cause a temulence‐like reaction in the tumor, significantly inhibiting tumor progression, and might provide an intelligent and nonsurgical substitute for PEI therapy. Abstract : Acetaldehyde generator SC@ZIF@ADH based on Saccharomyces cerevisiae can cause a temulence‐like reaction in the tumor and inhibit tumor progression.